Revision of the genus Prosaspicera Kieffer, 1907(Hym.: Figitidae: Aspicerinae) - Ros-Farré, P.; Pujade-Villar, J. (Zootaxa, 2006)
Prosaspicera Kieffer is an Aspicerinae genus (Hymenoptera: Cynipoidea: Figitidae) with a mostly Nearctic, Neotropical, Afrotropical and Oriental distribution. Prosaspicera is here cited from the Eastern Palaearctic (Japan) for the first time. Morphological features necessary to differentiate species of Prosaspicera are described. Although Prosaspicera brevispinosa Díaz, 1979, represents an atypical intraspecific variability that suggests it may be a species complex, other species of Prosaspicera are morphologically homogeneous. The type material of the 17 known species of Prosaspicera has been studied. Out of these 17 species, 15 are here considered as valid, since Prosaspicera africana (Kinsey, 1919) and P. kinsantua (Benoit, 1956) are both a syn nov. of P. tropica (Kieffer, 1910). These 15 valid species are here redescribed. The examination of hundreds of additional specimens supplied by different institutions suggests there is a general lack of knowledge concerning the species diversity of this genus. For the first time the males of P. optivus Quinlan, 1979, P. albihirta (Ashmead, 1887), P. pugionifera (Kieffer, 1907) and P. ueteri (Borgmeier, 1935) and, the females of P. aterrima (Kieffer, 1910) and P. validispina (Kieffer, 1910) are described. Fifteen new species are described: P. angustispina Ros-Farré sp. nov., P. carinata Pujade-Villar sp. nov., P. costulata Ros-Farré sp. nov., P. confusa Ros-Farré sp. nov., P. curvispina Ros-Farré sp. nov., P. dentata Pujade-Villar sp. nov., P. inaudita Ros-Farré sp. nov., P. joani Ros-Farré & Pujade-Villar sp. nov., P. kiefferi Ros-Farré sp. nov., P. mariarosae Ros-Farré & Pujade-Villar sp. nov., P. orientalis Pujade-Villar sp. nov., P. pseudoclavata Ros-Farré sp. nov., P. spinosa Ros-Farré sp. nov., P. splendida Ros-Farré sp. nov., and P. uniformis Ros-Farré sp. nov. A key to the 30 valid species of Prosaspicera is given. All species are thoroughly illustrated.